Flowchart Sistem Penagihan Pada Perusahaan Jasa Konsultan - Inge Handriani (Sekolah Tinggi Teknik - PLN, 2015)
Currently an industry if it is to be a sustainable company that life continues, then it must have a system that works is set operational standard operating procedures. Without such standards, the company does not have a handle in running the company. This problem will be felt when the company handle billing, therefore, to then be made to the system can handle billing system.On this system will set up the billing process to avoid cheating in it. All these systems are adapted to the conditions of the company from all sides. So that the system can be run in accordance with the requirements and conditions of the company.